Association between Life’s Essential 8 and Atherogenic Index of Plasma in adults: insights from NHANES 2007–2018 - Xu, Long-Hui; Ding, Kai-Wen; Yang, Guo-Dong; Han, Xiao-Xuan; Cong, Xiao; Wang, Rong-Hui; Liu, Xin-Ru; Li, Na; Xu, Cui-Ping (Frontiers in Endocrinology, 2025)
IntroductionCardiovascular Disease (CVD) has become a significant global public health challenge, contributing to rising mortality rates. This study aims to investigate the relationship between Life’s Essential 8 (LE8) and the Atherogenic Index of Plasma (AIP), providing insights into the assessment and improvement of Cardiovascular Health (CVH).MethodsWe conducted an analysis of data from 8,215 U.S. adults aged 20 years and older, utilizing the National Health and Nutrition Examination Survey (NHANES) data from 2007 to 2018. Based on the LE8 score, CVH was classified into three levels—low, moderate, and high—while AIP was classified into four risk levels: extremely low (AIP<-0.3), low (-0.3≤AIP<0.1), medium (0.1≤AIP<0.24), and high (AIP≥0.24). Weighted ordinal logistic regression analysis was utilized to examine the association between the LE8 score and the AIP risk level, adjusting for potential confounding variables.ResultsA significant negative correlation exists between the LE8 score and the AIP risk level (OR=0.51, 95%CI: 0.49-0.54, P<0.001). Higher CVH were associated with lower AIP risk levels, while lower CVH corresponded to elevated AIP risk levels. Notably, improvements in specific LE8 components—such as body mass index and blood lipids—exhibited a strong relationship with reductions in the AIP risk level.DiscussionThis study suggests that the LE8 may serve as a preventive factor for CVD risk and implies that individuals can actively regulate their metabolic characteristics by optimizing their lifestyle.